Social equity and the funding of community policing - Gutierrez, Ricky S., 1953- (Criminal justice (LFB Scholarly Publishing LLC), 2003)
This analysis of social equity and the solicitation and granting of federal funds will examine how police agencies have changed in lieu of the receipt of these funds authorized by the 1994 Federal Crime Bill. In the first part of this study, an analysis of the recent history of federal funding aimed at improving law enforcement capabilities will be examined. Next, the community oriented policing (COP) movement will be analyzed by detailing the types of programs subsidized by the 1994 Crime Bill funding, their original intent, and how they were to be operationalized will be discussed. A theoretical framework will be presented that will use empirical assessments of the number of community (or proactive) programs in place in each agency, degrees of organizational change noted in a three-year review of each department's structure as reported in the LEMAS survey of police departments, the levels of economic inequality present in the jurisdictions that received COP funding, and the ethnic composition of these jurisdictions.